Here is the question I am having trouble with:

Consider the quasilinear equation $u(x,t)$,

$u_t+uu_x=-\dfrac{1}{2u}$ with the initial condition $u(x,0)=\sin x$:

This is what I have so far:

Assume $u(x,t)$ is a solution.

Consider $h(t)=u(\xi(t),t)$, $h(0)=\sin x_0$


Let $\xi'(t)=u$, then $h'(t)=-\dfrac{1}{2u}=-\dfrac{1}{2h(t)}$ and therefore

$h(t)=e^{-\frac{t}{2}}\sin x_0$.

I'm not really sure where to go from here. Any help would be greatly appreciated!




Follow the method in http://en.wikipedia.org/wiki/Method_of_characteristics#Example:

$\dfrac{du}{ds}=-1$ , letting $u(0)=0$ , we have $u=-s$

$\dfrac{dt}{ds}=2u=-2s$ , letting $t(0)=t_0$ , we have $t=t_0-s^2=t_0-u^2$

$\dfrac{dx}{ds}=2u^2=2s^2$ , letting $x(0)=f(t_0)$ , we have $x=f(t_0)+\dfrac{2s^3}{3}=f(u^2+t)+\dfrac{2u^3}{3}$

$u(x,0)=\sin x$ :





$\therefore x=\sin^{-1}\sqrt{u^2+t}-\dfrac{2(u^2+t)^\frac{3}{2}}{3}+\dfrac{2u^3}{3}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.